DETERMINANTS OF ELDERLY LABOR SUPPLY IN WEST NUSA TENGGARA INDONESIA - Triana Pujilestari (Fakultas Ekonomi Universitas Negeri Jakarta, 2021)
Elderly residents have the opportunity not to work and enjoy leisure in their retirement. However, the labor force participation rate for the elderly in West Nusa Tenggara (NTB) Province in 2017 reached 50.23 percent.Therefore, to see this potential, this study was conducted with the aim of analyzing the supply of elderly workers in NTB based on demographic and social factors. The influence of demographic and social factors on the supply of labor for the elderly will be calculated based on the opportunities for the elderly to work or not work. The analysis in this study used binary logistic regression. The data is sourced from National Labor Force Survey (Sakernas) 2017. The results of the supply of elderly workers in NTB is influenced by age, education level, gender, status of the head of the household, and the area of ​​residence. Keywords: Elderly, Labor, Logistics Regression, West Nusa Tenggara